Ajuste de una función expologística a la evolución de la población total de México, 1930-1985 - Ordorica, Manuel (El Colegio de México A.C., 1990)
In demographic research, a great number of mathematical functions have been developed for the purpose of analyzing the dynamics of the total population, among which the exponential function, the Gompertz curve, and the logistic function can be mentioned. Nevertheless, none of these functions can be applied suitably to the case of Mexico, due to the fact that the assumptions underlying the above-mentioned mathematical representations do not correspond to the observed dynamics of the components of natural growth. The purpose of this article is to adjust a mathematical function to the evolution of Mexico's total population between 1930 and 1985, adequately reproducing the evolution of natality and mortality observed in that period.